Awareness of Side Effects of Corticosteroids among Users and Nonusers in Saudi Arabia - Alhumaidan Lama Saleh; Alghamdi Abdullrahman A; Almutairi Meshari Sanad L; Alsubaihi Abdulrahman Abdullah; Alrasheedi Sami M; Alkhdairi Ahmad; Alzweihary Ali M; Alrasheedi Majed Swailem; Alrasheedi Khaled Ali Mohammed; Alrashdi Mousa Nasser (Wolters Kluwer Medknow Publications, 2024)
BackgroundCorticosteroids are anti-inflammatory medications that are used to reduce inflammation and inhibit the immune system in a variety of disorders, including allergies, asthma, systemic lupus erythematous, eczema, inflammatory bowel disease, and swollen joints or muscles. The goal of this study was to assess the level of awareness and sources of information about the side effects of corticosteroids among the general population in Saudi Arabia. MethodsThis observational cross-sectional study was conducted in Saudi Arabia using an electronic questionnaire. A non-probability convenience sampling technique was used. Statistical Package for the Social Sciences (SPSS) was used for data analysis. ResultsThe study included 755 participants from Saudi Arabia (67.3% females and 32.7% males). Around 26.8% reported using corticosteroids, and 73.9% were aware of the side effects of glucocorticoids. Among steroid users (202 participants), the most common conditions were allergies (36.1%), asthma or chronic obstructive pulmonary disease (COPD) (21.8%), and skin diseases (27.7%). The majority of respondents (57.9%) used steroids for less than 2 weeks, and topical application (52.5%) was the most common form. Only 30.7% received information about side effects at the time of prescription. The most reported side effects were truncal obesity, moon face, skin thinning, bruising, and slower wound healing. ConclusionThis study highlights the importance of promoting awareness and knowledge regarding the side effects of corticosteroids in Saudi Arabia. While overall awareness levels were relatively satisfactory, specific side effects require further attention in educational efforts.